The Dynamics of Tourism, Economic Growth, and CO2 Emissions in Uzbekistan: An ARDL Approach - Qodirov, Azizjon; Urakova, Dilfuza; Amonov, Mirzoxid; Masharipova, Manzura; Ibadullaev, Ergash; Xolmurotov, Fozil; Matkarimov, Feruz (International Journal of Energy Economics and Policy, 2024)
In this study, we examined the impact of key macroeconomic variables on the sustainability of tourism in Uzbekistan using open data from the World Bank from 2000 to 2023. The selected variables for the study include the number of international tourists, GDP, CO2 emissions, and exchange rates. Considering the importance of climate issues in ensuring sustainable tourism, the study combines these factors using the autoregressive distributed lag (ARDL) model to assess their long-term relationships. We chose this model due to its flexibility in dealing with variables of different integration orders. The results of the bounds testing procedure confirm the existence of a long-term cointegration relationship between the dependent variable (international tourist arrivals) and the selected macroeconomic indicators. Specifically, the study results indicate that GDP growth, exchange rate fluctuations, and CO2 emissions positively affect tourist arrivals to Uzbekistan. The findings of this study underscore the importance of infrastructure development and macroeconomic stability in attracting international tourists while emphasizing the need for sustainable international practices to mitigate environmental impacts. This study contributes to understanding the complex interrelationship between tourism development and macroeconomic variables in the context of developing countries and aids decision-making in this area.